Efficacy and Safety of Lurasidone in Children and Adolescents: Recommendations for Clinical Management and Future Research - Amerio, Andrea; Giacomini, Costanza; Fusar-Poli, Laura; Aguglia, Andrea; Costanza, Alessandra; Serafini, Gianluca; Aguglia, Eugenio; Amore, Mario (Current Pharmaceutical Design, 2021)
Lurasidone is a novel azapirone derivative and atypical antipsychotic agent with a high binding affinity for dopaminergic (D2), serotoninergic (5-HT2A), and 5-HT7 receptors (antagonist), a moderate affinity for 5- HT1A receptors (partial agonist), and no appreciable affinity for histaminergic (H1) and muscarinic (M1) receptors. It was recently included by the European Medication Agency among the in-label pharmacological treatments for children and adolescents affected by early onset schizophrenia. As a dopamine and serotonin antagonist, lurasidone acted on a variety of receptors and showed its efficacy both as an antipsychotic and an activating compound. Administered with food or within 30 minutes from a meal, it presents sufficient bioavailability and does not interact with most of the other drugs during metabolism. With little effects on hormones and weight gain, potential procognitive profile due to its 5-HT7 antagonism, and reduced extrapyramidal side effects, lurasidone could be a good choice in terms of both effectiveness and tolerability, particularly for patients headed towards a long-term treatment. This article aims to summarize the available scientific evidence from the literature on the use of lurasidone in children and adolescents and to provide recommendations for clinical management and future research.
Keywords: Adolescents